Analisis Tanggung Jawab Sosial Media Komunitas dalam Habitus Komunikasi Konvergen - Ika Yuliasari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The advancement of information and communication technology during the Industry 4.0 and Society 5.0 eras has brought significant changes to community media practices, especially in rural areas. This study examines the roles and social responsibilities of community radios CDR FM in Bantul, Yogyakarta, and RASI FM in Garut, West Java, amid the dynamics of digital media convergence. Employing a qualitative approach with a constructivist paradigm, data were collected through interviews, observations, focus group discussions, and documentation. The findings reveal that both community radios maintain their existence through active community participation, adaptation to digital technology, and management grounded in local values. Digital media convergence enables the expansion of broadcast reach from local to global levels, enhancing interaction and social mobilization. The social responsibility of community media is reflected in delivering factual information, shaping public opinion, preserving culture, and ensuring accountability to the audience. Key challenges include the regeneration of media activists and funding, which can be addressed by strengthening partnership networks and human resource capacity. This study confirms that community media play a strategic role as agents of social development in rural areas by leveraging evolving communication technologies.